Interpretation of Cuneiform Mathematics - Bruins, Evert M.
1. General remarks and new facts in number-representation 2. Linear equations 3. Quadratic equations 4. Computational aids and techniques 5. Geometry. 6. Soluble problems. Number theoretical results 7. Heronic triangles in Old Babylonian Mathematics 8. Euclid and the angle 9. The geometry of the plummet 10. Numerical data; 341 = riassunto italiano.